1967
DOI: 10.1063/1.1708978
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Resonance in Semiconducting Diamonds

Abstract: Electron spin resonance (ESR) was studied in five semiconducting diamonds in the temperature range 108°-370oK and at 4.2°K. The g factor is 2.0030±0.OOO3, and the linewidth varies from 0.3 to 8 Oe at room temperature. The number of spins contributing to the ESR absorption varies between 10 1 3-10 14 and agrees with the number of uncompensated acceptors in the case of two diamonds on which Hall and resistivity measurements were made. The number of spins varies as liT in the temperature range 108°-370oK. The spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The fact that in small diamonds which they were able to stress, an increase in the amplitude was observed rather than a shift is attributed to the external stress enlarging the volume of the crystal experiencing the predominantly grown-in stress. They did not observe the sharp line ( A H = 1 G) observed by Bell and Leivo (1967) for natural semiconducting diamond which was attributed by them to acceptor centres, on the basis that the number of acceptors obtained by Hall and resistivity measurements was comparable to the number of spins measured in these natural stones by ESR.…”
Section: = G P H J+ Djz2mentioning
confidence: 83%
See 1 more Smart Citation
“…The fact that in small diamonds which they were able to stress, an increase in the amplitude was observed rather than a shift is attributed to the external stress enlarging the volume of the crystal experiencing the predominantly grown-in stress. They did not observe the sharp line ( A H = 1 G) observed by Bell and Leivo (1967) for natural semiconducting diamond which was attributed by them to acceptor centres, on the basis that the number of acceptors obtained by Hall and resistivity measurements was comparable to the number of spins measured in these natural stones by ESR.…”
Section: = G P H J+ Djz2mentioning
confidence: 83%
“…It is now, however, clear that the spectrum is not due to aluminium but to an aggregate of three nitrogen atoms. Bell and Leivo (1967) found a fairly broad line in natural semiconducting diamonds which they attribute to the acceptors in the natural semiconducting diamond. Since then it has been established that the acceptors must be boron Williams 1971, Chrenko 1973).…”
Section: Acceptov Impuritiesmentioning
confidence: 98%
“…In the semiconducting diamonds, an EPR spectrum of the center has been observed similar to an acceptor of the p-type. No hyperfine structure (STS) has been identified (Bell and Leivo, 1967). Smith, Gelles and Sorokin (1959) have reported an observation of the EPR spectrum, representing a gap in the Al-C grouping (the hyperfine structure (STS) has been observed from the Al^7 isotope).…”
Section: International Geology Reviewmentioning
confidence: 96%
“…A review summarizing all of them can be found here [70]. The early work of Bell and Leivo [71] shows the estimated spin-lattice relaxation rate in semiconducting diamonds of the order 100 MHz (at 300 K) using the Bloch method [72]. The EPR center was associated with p-type donors.…”
Section: Many Different Paramagnetic Centers Occur Naturally After Ir...mentioning
confidence: 99%